Rozpad drzewostanu i odnowienie świerka a struktura i dynamika karpackiego boru górnoreglowego [Breakdown of tree stand and spruce regeneration versus structure and dynamics of a Carpathian subalpine spruce forest] - Holeksa, Jan (Monographiae botanicae, 2014)
Structure and dynamics of the Carpathian subalpine spruce forest was a subject of research conducted in Babia Góra National Park, protecting the highest massif in the whole West Beskids. The mosaic structure was simultaneously treated as a background for and a result of breakdown of spruce stand and spruce regeneration. The forest texture, dead trees, gaps, synusia of herb layer and spruce saplings were mapped over the area of 14,4 ha. Simultaneous mapping over the same and large area madę it possible to analyse the spatial relationships between all these phenomena and to reveal strong dependence between most of them. Particular attention was focused on spruce regeneration. It was stated that young spruces arę closely linked to microsites created by death of trees: windthrow mounds, logs and stumps in advanced stage of decay, and gaps larger than 200 m2. Seedlings and saplings were also relatively more abundant in patches dominated in herb layer by Vaccinium myrtillus or Dryopteris dilatata than in others. The conclusion was achieved that coarse-grained type of mosaic structure in subalpine spruce forest and large-scale disturbances not only arę the result of low resistance of congeneric and one-layered tree stands against wind, snów, glaze and insects. To large degree they are also shaped by condition of spruce regeneration. As a light-demanding species, spruce at high elevation needs large gaps for successfull regeneration. It leads to excessive thinning of stands and expose them to disruptive action of harsh climat in the subalpine forest belt.